MODEL MANAJEMEN PELAYANAN GIZI KOMPLEMENTER TERINTEGRASI DALAM UPAYA PENINGKATAN STATUS GIZI MASYARAKAT - Arina Nurul Ihsani; Chindy Amir; Conita Afriani (Indonesian Journal of Thousand Literacies, 2023)
Nutritional problems remain a significant public health issue in Indonesia, particularly among vulnerable groups such as infants, toddlers, pregnant women, and breastfeeding mothers. Various nutritional indicators indicate a persistently high burden of malnutrition, despite a downward trend in recent years. The national prevalence of stunting among toddlers was recorded at 19.8% in 2024, although still higher than the national target of <14% at the end of the 2024–2029 National Medium-Term Development Plan (RPJMN). Wasting and underweight also remain challenges, at approximately 7.4% and 16.8%, respectively, in children under five. Furthermore, anemia and chronic energy deficiency in pregnant women continue to contribute to the risk of low birth weight.Complementary nutrition services, as a nutritional intervention strategy, play a crucial role in meeting additional nutritional needs through planning, organizing, implementing, monitoring, and evaluating. The implementation of integrated service management involving cross-sectoral collaboration, community empowerment, and utilization of local food resources increases service effectiveness and program coverage. The use of an integrated approach also significantly increased energy and protein intake in malnourished toddlers in a quasi-experimental study (n=140), showing significant increases in energy (difference-in-differences [DID] = 405.53 kcal; p<0.001) and protein (DID = 4.62 g; p<0.001). This model has the potential to improve the nutritional status of the community sustainably if implemented consistently and in a coordinated manner.